A rare case of congenital leukemia: acute myeloblastic leukemia in a neonate with Down syndrome - Anitha G., Fatima Shirly; Darlington C, Danny (International Journal of Contemporary Pediatrics, 2016)
Congenital leukemia is an exceedingly uncommon disease in newborn and is usually diagnosed at birth or within one month of life. It is usually associated with a fatal outcome. Neonates with Down syndrome have an increased risk of congenital leukemia. Because of the rapid doubling time of leukemic cells, the disease becomes clinically evident at birth or shortly thereafter. We report a case of congenital leukemia in a newborn with Down syndrome, the diagnosis of which was established with strong clinical suspicion and confirmed with haematological investigations.